Digital Marketing Application to Increases Livestock Sales in Sacrificial Cages in Ganggang Panjang Sidoarjo Village Based on Android: Aplikasi Digital Marketing Meningkatkan Penjualan Ternak pada Kandang Qurban di Desa Ganggang Panjang Sidoarjo Berbasis Android - Refinda, Achmad Ainun Gusti; Fitrani, Arif Senja (Universitas Muhammadiyah Sidoarjo, 2023)
The need for qurban animals both for the needs of the Eid al-Adha holiday and needs other than Eid al- Adha such as aqiqah, or other important events are very much needed where in the selection of sacrificial animals such as goats or cows are both very important. types of sacrificial goats and cows, the condition of the sacrificial animals so that the results given are very good. In the process of selecting, purchasing, distributing sacrificial animals, they still use the manual method, which is less efficient, so there is a need for an application system that can assist in selecting, purchasing, and distributing sacrificial animals. In running the business, most of the service processes that are applied are still manual by checking the condition of the animal by coming to the place so that it is difficult for the customer to come twice or contact by phone. Then, in managing transaction data and issuing notes, it is also still manual.